Development and evaluation of a didactic tool with augmented reality for Quechua language learning in preschoolers - Joselyn Zapata-Paulini; Saul Beltozar-Clemente; Fernando Sierra-Liñan; Michael Cabanillas-Carbonell (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
It is important to preserve our cultural identity through the preservation of our mother tongue, contributing to its dissemination. Augmented reality (AR) is a great ally of education that provides efficiency, and productivity and increases the interest of students in their academic activities. An AR application was developed for learning Quechua in preschool children, thus improving their learning, satisfaction, and preference compared to traditional teaching. Previously, learning styles were identified for better coverage of the application; the design thinking methodology was applied for the development of the application, then the respective tests were conducted where it was obtained that the children's performance improved by 28.3% more compared to traditional teaching, with an average satisfaction of 89% of the classrooms, and 81% of students' preference. It was concluded that the proposed application considerably favors the written and audiovisual learning of the Quechua language in preschool students.